In vitro Dissolution Profile at Different Biological pH Conditions of Hydroxychloroquine Sulfate Tablets Is Available for the Treatment of COVID-19 - Dongala, Thirupathi; Katari, Naresh Kumar; Ettaboina, Santhosh Kumar; Krishnan, Anand; Tambuwala, Murtaza M.; Dua, Kamal (Frontiers in Molecular Biosciences, 2021)
Hydroxychloroquine sulfate is one of an extensive series of 4-aminoquinolines with antimalarial activity. Moreover, it is used for the treatment of rheumatoid arthritis. Sometimes Hydroxychloroquine sulfate is beneficial for the treatment of autoimmune diseases. Based on the recent clinical experiments, it is exploiting for the treatment of COVID-19, coronavirus across the globe. The chromatogram separation was achieved by using Agilent, Zorbax C8, 250 x 4.6 mm i.d., column. The buffer consists of 0.01M of 1-pentane sulfonic acid and 0.02% of Orthophosphoric acid in purified water. Mixed buffer, acetonitrile and methanol (800: 100: 100 v/v). The flow rate was 1.0 mL min-1 and injection volume was 10 µl. Detection was made at 254 nm by using a dual absorbance detector (DAD). The RP-HPLC method has been developed and validated as per the current ICH guidelines to estimate Hydroxychloroquine sulfate tablets. As part of method validation performed, specificity, linearity, precision, and recovery parameters. The concentration and area relationships were linear (R2 > 0.999), over the concentration range of 25 to 300 µg mL-1 for HCQ. The relative standard deviations for precision and intermediate precision were less than 1.5%. The proposed RP-HPLC generic method was applied successfully to evaluate the in-vitro dissolution profile with different pH conditions like 0.1N HCl, pH 4.5 Acetate buffer, and pH 6.8 Phosphate buffers of US marketed reference product.